A new scale measuring coaches` unethical behaviors for comparison by gender, age, and education level of coach - Dolasir Tuncel, S. (The Sport Journal, 2009)
An effort to develop a scale measuring coaches` unethical behaviors included two phases. In the first, factor and reliability analyses were made of potential survey items meant to gather data from athletes describing coaches` behavior. In the second, select items were incorporated in a survey randomly administered to 221 male and female taekwondo competitors at a national competition in 2006, for comparison of behaviors by coach gender, age, and education. Behavior was not found to differ significantly by gender (n = 219, t = 1.71, p > .05), age (n = 216, t = 1.13, p > .05), or education (n = 217, t = 1.60, p > .05).